2021
DOI: 10.3389/fmars.2021.773481
|View full text |Cite
|
Sign up to set email alerts
|

Low Dose-Rate Irradiation of Gamma-Rays-Induced Cytotoxic and Genotoxic Alterations in Peripheral Erythrocytes of p53-Deficient Medaka (Oryzias latipes)

Abstract: Morphological alterations and nuclear abnormalities in fish erythrocytes have been used in many studies as bioindicators of environmental mutagens including ionizing radiation. In this study, adult Japanese medaka (Oryzias latipes) were irradiated with gamma rays at a low dose rate (9.92 μGy/min) for 7 days, giving a total dose of 100 mGy; and morphological alterations, nuclear abnormalities, and apoptotic cell death induced in peripheral erythrocytes were investigated 8 h and 7 days after the end of the irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Schistocytes can occur in acquired and inherited red blood cell disorders, reflecting significant abnormalities in cell shape and size [163]. While being rarely present, studies have indicated the occurrence of schistocytes in fish, particularly under the influence of irradiation and gamma rays [71]. Fish with higher levels of unsaturated fatty acids in their membranes were found to be more susceptible to lipid peroxidation and erythro‐membrane damage following gamma radiation [164].…”
Section: Types Of Poikilocytosis In Fishmentioning
confidence: 99%
“…Schistocytes can occur in acquired and inherited red blood cell disorders, reflecting significant abnormalities in cell shape and size [163]. While being rarely present, studies have indicated the occurrence of schistocytes in fish, particularly under the influence of irradiation and gamma rays [71]. Fish with higher levels of unsaturated fatty acids in their membranes were found to be more susceptible to lipid peroxidation and erythro‐membrane damage following gamma radiation [164].…”
Section: Types Of Poikilocytosis In Fishmentioning
confidence: 99%